Hypoxia and Angiogenesis in Endometrioid Endometrial Carcinogenesis - Nicole Horrée; Paul J. van Diest; Petra van der Groep; Daisy M. D. S. Sie-Go; A. Peter M. Heintz (Cellular Oncology)
Background: Hypoxia-inducible factor 1α (HIF-1α) plays an essential role in the adaptive response of cells to hypoxia, triggering biologic events associated with aggressive tumor behavior. Methods: Expression of HIF-1α and proteins in the HIF-1α pathway (Glut-1, CAIX, VEGF) in paraffin-embedded specimens of normal (n = 17), premalignant (n = 17) and endometrioid endometrial carcinoma (n = 39) was explored by immunohistochemistry, in relation to microvessel density (MVD). Results: HIF-1α overexpression was absent in inactive endometrium but present in hyperplasia (61%) and carcinoma (87%), with increasing expression in a perinecrotic fashion pointing to underlying hypoxia. No membranous expression of Glut-1 and CAIX was noticed in inactive endometrium, in contrast with expression in hyperplasia (Glut-1 0%, CAIX 61%, only focal and diffuse) and carcinoma (Glut-1 94.6%, CAIX 92%, both mostly perinecrotically). Diffuse HIF-1α was accompanied by activation of downstream targets. VEGF was significantly higher expressed in hyperplasias and carcinomas compared to inactive endometrium. MVD was higher in hyperplasias and carcinomas than in normal endometrium (p < 0.001). Conclusion: HIF-1α and its downstream genes are increasingly expressed from normal through premalignant to endometrioid adenocarcinoma of the endometrium, paralleled by activation of its downstream genes and increased angiogenesis. This underlines the potential importance of hypoxia and its key regulator HIF-1α in endometrial carcinogenesis.